Changes in the prevalence, treatment and control of hypertension in Germany?: a clinical-epidemiological study of 50.000 primary care patients - Labeit, Alexander; Wehling, Martin (PLOS ONE, 2012)
Introduction: Medical societies have developed guidelines for the detection, treatment and control of hypertension (HTN). Our analysis assessed the extent to which such guidelines were implemented in Germany in 2003 and 2001. Methods: Using standardized clinical diagnostic and treatment appraisal forms, blood pressure levels and patient questionnaires for 55,518 participants from the cross-sectional Targets and Essential Data for Commitment of Treatment (DETECT) study (2003) were analyzed. Physician’s diagnosis of hypertension (HTNdoc) was defined as coding hypertension in the clinical appraisal questionnaire. Alternative definitions used were physician’s diagnosis or the patient’s self-reported diagnosis of hypertension (HTNdoc,pat), physician’s or patient’s self-reported diagnosis or a BP measurement with a systolic BP≥140 mmHg and/or a diastolic BP≥90 (HTNdoc,pat,bp) and diagnosis according to the National Health and Nutrition Examination Survey (HTNNHANES). The results were compared with the similar German HYDRA study to examine whether changes had occurred in diagnosis, treatment and adequate blood pressure control (BP below 140/90 mmHg) since 2001. Factors associated with pharmacotherapy and control were determined. Results: The overall prevalence rate for hypertension was 35.5% according to HTNdoc and 56.0% according to NHANES criteria. Among those defined by NHANES criteria, treatment and control rates were 56.0% and 20.3% in 2003, and these rates had improved from 55.3% and 18.0% in 2001. Significant predictors of receiving antihypertensive medication were: increasing age, female sex, obesity, previous myocardial infarction and the prevalence of comorbid conditions such as coronary heart disease (CHD), hyperlipidemia and diabetes mellitus (DM). Significant positive predictors of adequate blood pressure control were CHD and antihypertensive medication. Inadequate control was associated with increasing age, male sex and obesity. Conclusions: Rates of treated and controlled hypertension according to NHANES criteria in DETECT remained low between 2001 and 2003, although there was some minor improvement.